Board Gender Diversity and its Impact on Firm Risk-Taking - Hesniati, Hesniati; Vernando, Lovis; Haryanto, Hery; Arviano, Hengky (JDM (Jurnal Dinamika Manajemen), 2024)
This study aims to analyze the gender diversity of boards of directors and its impact on firm risk-taking. It is interesting to study because the presence of women on the board of directors of a firm has garnered considerable attention in the last few years. The sample is drawn from the industrial sector listed on the Indonesian Stock Exchange from 2017 to 2021. Firm risk-taking is measured by the volatility of stock returns. Using panel data, the results of the research indicate that gender diversity has a significantly positive impact on firm risk-taking. This finding contributes that a female board of directors would lead to greater risk-taking than their male counterparts. This research provides a literature on gender diversity and firm risk-taking in a male-dominated sector in Indonesia, providing insights for investors and companies to consider the potential benefits of gender diversity on board of directors in managing firm risk-taking. Further research could apply other measurements of firm risk-taking and observe other male-dominated sectors for comparison to enhance the study’s limitation.